2019
DOI: 10.31703/grr.2019(iv-iv).50
|View full text |Cite
|
Sign up to set email alerts
|

Media Bias Effects on Voters in Pakistan

Abstract: The news media play a significant role in shaping political opinions and party choices of voters as most of the people learn about politics through media. The study investigated the influence of television news channels' biases over the voting behavior of the electorates. The survey method was used as a tool for data collection to determine the relationship between media bias and its influence on voting behavior. Partisan views are exposed when news channels give one side of the political spectrum a distinct a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Pakistan's expenditure per soldier is 5,900 dollars annually, about one-tenth of South Africa's (53,500 dollars) and below the annual UN reimbursement (17,136 dollars). The profiles of these countries as UN troop contributors mention economic incentives in Pakistan's case but not in South Africa's case (Malik, 2014;Lotze & de Coning, 2015), a possible reason why Pakistan deploys its peacekeepers about twice as fast as South Africa. 10 Proposition 1995/96:113 and parliamentary debate 15 December 1995 (96: 39).…”
Section: Resultsmentioning
confidence: 99%
“…Pakistan's expenditure per soldier is 5,900 dollars annually, about one-tenth of South Africa's (53,500 dollars) and below the annual UN reimbursement (17,136 dollars). The profiles of these countries as UN troop contributors mention economic incentives in Pakistan's case but not in South Africa's case (Malik, 2014;Lotze & de Coning, 2015), a possible reason why Pakistan deploys its peacekeepers about twice as fast as South Africa. 10 Proposition 1995/96:113 and parliamentary debate 15 December 1995 (96: 39).…”
Section: Resultsmentioning
confidence: 99%
“…Media frames and shapes the political agenda that, in turn, greatly affects the politics and the voter's political affiliations. A study conducted in Pakistan found that the media had a significant impact on the voters' political inclination, and that impact was due to the framing of news by the media as it can play up or play down any news affecting its news value tremendously (Ali & Rahman, 2019). Newspaper editorials are an important part of a newspaper as they represent the newspaper's policy and its political affiliation.…”
Section: Relevant Literaturementioning
confidence: 99%
“…In Pakistan, the media faces several allegations of political bias, and it has been evident in the past that media succumbed to external pressures and was unable to withhold its objectivity (Rehmat 2018). For the smooth working of a democracy, we need independent media as media plays a crucial role in forming the voting behavior of the citizens; therefore, media bias in reporting will bring with it severe repercussions (Ali & Rahman, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, this leads to a social problem as the events are reported subjectively to serve a hidden ideology. Ali & Rahman (2019) defined bias as when the news reporters write news articles in a prejudiced or partial way in order to assist a specific political party. In this paper, the researcher defines 'bias' as A tendency and/or prejudice of a person or group 'X' against a person or group 'Y,' by focusing on or neglecting a particular area either by supporting or opposing it, due to power abuse, to achieve hidden ideology or interest.…”
Section: Introductionmentioning
confidence: 99%